Psychological Preparedness for Disasters and Adaptive Performance of Student Volunteers in Handling the Covid-19 Pandemic at Padjadjaran University - Yunita Anggraeni; Retno Hanggarani Ninin; Sri Rahayu Astuti (Psycho Holistic, 2021)
Student volunteers who are members of the handling of the COVID-19 pandemic in Padjadjaran University aim to help students affected by the COVID-19 pandemic. The impact of the pandemic which resulted in physical and psychological problems that aroused the desire to help from student volunteers. This study aims to determine the relationship between psychological preparedness and adaptive behavior in student volunteers. This study uses a quantitative approach using a questionnaire as a research instrument. The study was carried out on 53 student volunteers who are members of the handling of the covid-19 pandemic. The data was processed using the Pearson's correlation statistical test and the results obtained r = 0.655 (ρ 0.000 < 0.05) which means that there is a positive and significant relationship between psychological preparedness to face disasters and the adaptive behavior of student volunteers. Student volunteers have the intention to become volunteers in the future with experience from handling the COVID-19 pandemic.